PENINGKATAN KEAKTIFAN SISWA KELAS III SEKOLAH DASAR PADA PEMBELAJARAN IPAS MELALUI MEDIA INTERAKTIF WORDWALL - Jannah, Miftahul; Ayu Prima Pravitasari; Yuni Dwi Astuti; Ratnasari Dyah Utami; Suprapti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research based on low students active learning of third grade SDN Kleco 1 Surakarta. Students often passive on learning and not active during class. Low active learning seen on lack of students interaction and completing assignments. This research is Class Action Research (CAR) that aim to increase students active learning on IPAS subject through Wordwall media. This research subject consisted of third grade students on SDN Kleco 1 Surakarta. This research method was conducted of two cycle with. Data collecting through observation and documentation is describe with increasing active learning percentage calculation, then compare with success indicator which is above 75%. Through data collecting show that there’s improvement of 65,19% students had high active learning from cycle I, then improve with 86,88% in cycle II. Based on this result show that Wordwall media is effective to improve third grade students active learning on IPAS subject.